1977
DOI: 10.1136/vr.100.26.550
|View full text |Cite
|
Sign up to set email alerts
|

Cases of prolonged luteal activity in the non-pregnant dairy cow

Abstract: Regular measurements of progesterone in milk were made to monitor ovarian activity in over 300 commercial dairy cows from partiurition until pregnancy established. Six animals (approximately 1-5 per cent) which had not previously been inseminated showed prolonged luteal activity lasting for over 30 days. No apparent uterine abnormalities or infections were found in these cases. Prostaglandin analogue cloprostenol (Estrumate ICI) given intramuscularly induced complete luteolysis in treated animals. The subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Moreover, follicles in cows affected with severe negative energy balance (greater BCS loss) were reported to be smaller in size and produce less estrogen [1]. However, some studies indicated that the occurrence of PLP has not been associated with any obvious clinical reproductive disorders [3,14]. A high incidence of prolonged luteal phase after insemination in cows with prolonged luteal activity after first ovulation was reported previously [9].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, follicles in cows affected with severe negative energy balance (greater BCS loss) were reported to be smaller in size and produce less estrogen [1]. However, some studies indicated that the occurrence of PLP has not been associated with any obvious clinical reproductive disorders [3,14]. A high incidence of prolonged luteal phase after insemination in cows with prolonged luteal activity after first ovulation was reported previously [9].…”
Section: Discussionmentioning
confidence: 98%
“…A persistent CL was defined as a luteal structure that remained detectable in the ovary for >30 d and maintained serum progesterone concentrations >1 ng/ mL (Bulman and Lamming, 1977). A short luteal phase was defined as an interval between first and second postpartum ovulation of <12 d. Anovulation was defined as no ovulation for the entire 70-d postpartum period.…”
Section: Postpartum Ultrasound Evaluation and Reproductive Managementmentioning
confidence: 99%
“…Corpora lutea (or possibly ovarian structures which are not true corpora lutea) which persist for longer than normal are not uncommon in the early post-partum period (Bulman & Lamming, 1977); also ovulations without preceding oestrous behaviour, but with formation of apparently normal corpora lutea are common. These abnormalities are detectable with the aid of milk progesterone levels and may then be effectively treated with prostaglandin F 2a or cloprostenol, a synthetic analogue of prostaglandin F 2a , which induces regression of corpora lutea and permits new ovulations to occur.…”
Section: Research On Hormonal Therapy For Reproductive Disordersmentioning
confidence: 99%